Academic language in second language learning - Faltis, Christian; Arias, M. Beatriz (Emerald Publishing Limited : Information Age Publishing, Inc., 2013)
This volume sheds new light on the question of a "Soviet model" by examining how a particular Soviet system of science and higher education emerged, how it was exported and imported across varying local, national and international settings, and how key aspects of it outlived the political system that fostered it. The contemporary crises in science and higher education surrounding the demise of communism appear as a distinctive break from the patterns set into motion in the 1920s and 30s, but also as one more upheaval following a long line of previous reorderings throughout the 20th century that were conditioned by broader cataclysms in politics, society, ideology, and culture.